The Arabidopsis E3 ubiquitin ligase PUB13 synergistically interacts with BON1 to regulate plant flowering and immunity - Yue, Jiani; Zou, Xiuwei; Peng, Yu; Pan, Sujun; Hu, Cailin; Wang, Bing; Dai, Liangying; Li, Wei (Frontiers in Plant Science, 2025)
The ubiquitination pathway is extensively involved in the regulation of plant biological processes, such as growth, development, and disease resistance, among others. Our previous study showed that the Arabidopsis U-box protein PUB13 regulates plant cell death, immunity, and development. Here, we report that the E3 ubiquitin ligase activity of PUB13 is required for its regulation of the plant size, flowering time, and immunity based on the analysis of the biological processes on the PUB13 enzyme activity loss mutant. Furthermore, we identified the copine protein BON1 interacting with PUB13, which was ubiquitinated by PUB13. Interestingly, the knockout of BON1 in the pub13 mutant further strengthens its phenotypes of retarded growth and early flowering. In addition, the knockout of BON1 further enhanced the resistance of pub13 to the biotrophic pathogen. In contrast, the pub13bon1 double mutant was more susceptible to the necrotrophic pathogen compared with the pub13 and bon1 single mutants. The synergistic effect between PUB13 and BON1 was also observed in the regulation of pathogen-associated molecular pattern-triggered immunity (PTI). These results indicate that the E3 ubiquitin ligase activity is required for PUB13 regulating biological functions and that BON1 synergistically interacts with PUB13 to regulate plant growth, flowering, and immunity in Arabidopsis.